Analysis of Strategies and Success Factors of Fishers Social Movement - Charity Naysa Nasution; Rilus A. Kinseng; Soeryo Adiwibowo (JURNAL ILMU SOSIAL, 2019)
The sources of social change are diverse; one of which is the social movement. The study of social movements is essential for understanding contemporary society and the direction of its movement. Whether or not a movement is massive does not hide the reality that social movements can change history, sometimes by causing significant changes. The emergence of social movements is not sudden but determined by various factors, such as political opportunities, mobilization structures, and framing processes. A new factor which becomes the focus of the present study is related to the complexity of the actors involved in a social movement. This focus is important, given the mapping of strengths and roles of actors who have networked in different spheres of power has its benefits in order to analyze the dynamics of social movements. This study aims to analyze the success factors of the fishers’ social movement and the roles of actors in determining the strategy of the movement, which can influence the results. This research used a mixed-method that involves a combination of qualitative and quantitative approaches. The results showed that actors in the social movement of fishers were divided into five layers with a hierarchical structure, while each layer had different roles and responsibilities. Furthermore, mobilized resources include moral resources, material resources, socialorganizational resources, and human resources.